2010
DOI: 10.1016/j.jcin.2009.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Flow Reserve and Myocardial Perfusion Imaging in Patients With Angiographic Multivessel Coronary Artery Disease

Abstract: Myocardial perfusion imaging with single-photon emission computed tomography has poor concordance with FFR and tends to underestimate or overestimate the functional importance of coronary stenosis seen at angiography in comparison with FFR in patients with multivessel disease. These findings might have important consequences in using MPI to determine the optimal revascularization strategy in patients with multivessel coronary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(136 citation statements)
references
References 31 publications
5
124
1
6
Order By: Relevance
“…However, we found that the assessment of stress‐rest perfusion CMR alone showed limited diagnostic concordance in predicting reduced FFR in multivessel disease. This is supported by the results by Melikian et al, who reported that the sensitivity and specificity of myocardial perfusion single‐photon emission computed tomography for detecting significant stenosis was 76% and 38%, respectively, in patients with multivessel disease 20. In contrast to single‐photon emission computed tomography, first‐pass stress‐rest perfusion CMR can theoretically reveal abnormal transmural blood flow patterns, thus avoiding false‐negative results that can occur in balanced myocardial ischemia in multivessel disease.…”
Section: Discussionsupporting
confidence: 79%
“…However, we found that the assessment of stress‐rest perfusion CMR alone showed limited diagnostic concordance in predicting reduced FFR in multivessel disease. This is supported by the results by Melikian et al, who reported that the sensitivity and specificity of myocardial perfusion single‐photon emission computed tomography for detecting significant stenosis was 76% and 38%, respectively, in patients with multivessel disease 20. In contrast to single‐photon emission computed tomography, first‐pass stress‐rest perfusion CMR can theoretically reveal abnormal transmural blood flow patterns, thus avoiding false‐negative results that can occur in balanced myocardial ischemia in multivessel disease.…”
Section: Discussionsupporting
confidence: 79%
“…19 Fractional flow reserve is more accurate than coronary angiography to assess the physiologic significance of a stenosis, and in the current era, fractional flow reserve is the gold standard for diagnosing the significance of CAD. 20,21 Our results of 473 radionuclide pharmaceutical stress tests in patients with ESLD suggest that a standard risk factor assessment provides results that are equivalent to those of radionuclide imaging studies. This risk stratification can be obtained without the additional radiation and expense to patients of radionuclide imaging.…”
Section: Discussionmentioning
confidence: 78%
“…We concluded that additional endogenous stress due to coronary ischemia led further increment in post-exercise copeptin levels. This finding can be very beneficial especially in false negative cases such as normal perfusion scintigraphy due to balanced ischemia in multivessel CAD [3,4]. Confirmation of increased copeptin level at post-exercise can guide physician accordingly to apply further diagnostic interventions.…”
Section: Discussionmentioning
confidence: 92%
“…A false negative result can be obtained in the SPECT MPS due to balanced multiple vessel disease. Thus, nearly 13-15% of patients with left main disease can have normal perfusion scintigraphy due to balanced ischemia in multivessel CAD [3,4]. Other disadvantages in MPS are equivocal results due to attenuation artifacts, patient positional movement during the test, or incorrectly applied technical analyses.…”
Section: Introductionmentioning
confidence: 99%